Get a Teaching Job NOW: A Step-by-Step Guide - Clement, Mary C. (Rowman & Littlefield Publishers, 2013)
There ARE jobs for teachers, and this step-by-step guide will help college students and career changers find those jobs and get them. Whether you seek a job as a substitute teacher or full-time pre-school, elementary, middle, or high school teacher, the strategies needed to win a job are here. The job market has changed, and teachers no longer get jobs just by just student teaching in a school. Today’s candidates need to use online search engines to find openings, and then produce a cover letter, resume, and portfolio that showcases their training. Interviewing is much more than answering the question, “Tell me about yourself.” Teacher candidates must master the art of the behavior-based interview to sell their experience and expertise to employers. When a candidate’s Facebook page can make or break hiring, everything a potential new teacher does is important.